Analysis of Health-Seeking Behavior Factors in Coronary Heart Disease Patients - Bakar, Abu; Widiyanti, Risma Listya; Harmayetty, Harmayetty (Critical Medical and Surgical Nursing Journal, 2023)
Introduction: Indonesian Research of Basic Health 2019 show that 1.5% of Indonesia's population suffers from coronary heart disease (CHD). Coronary heart disease has an impact on all aspects of the patient's life. Good health-seeking behavior is expected to prevent the severity from getting worse, and the risk of complications, up to death. This study aims to analyze the relationship between knowledge, attitudes, perceptions about health-illness and the ease of access to health service providers with health-seeking behavior in CHD patients. Methods: This study used a correlational descriptive design with a cross sectional approach. The population is CHD patients who are registered in the 3 work areas of the Gresik District Health Center. A large sample of 80 patients, using a purposive sampling technique. This study used questionnaires of health-seeking behavior in CHD patients, knowledge, attitude, perception about health-illness, and a questionnaire to measure the the ease of access to health service providers. Data analysis used the Spearman Rho test. Results: Major partial CHD affects patients aged 46-55 years and of good sex. There is a relationship between knowledge and health-seeking behavior in CHD patients (p = 0.001 and r = 0.367), there is a relationship between attitudes and health-seeking behavior in CHD patients (p = 0.000 and r = 0.737) and there is a relationship between perceptions of illness and health-seeking behavior in CHD patients (p = 0.001 and r = 0.361). Conclusion: The higher the knowledge and perceptions about illness and health, the more supportive the patient's attitude will be, and the better the health-seeking behavior in CHD patients. It is hoped that education and assistance can be given to CHD patients so they are more aware of the importance of appropriate treatment behavior.